How do rigid labor markets absorb immigration? Evidence from France - Anthony Edo (IZA Journal of Migration, 2016)
This paper investigates how immigration can affect the labor market outcomes of native workers when their wages are rigid. I use a rich dataset for France and decompose the native workers according to whether they are covered by fixed-term or indefinite-term contracts. Indefinite-term contracts are associated with higher wage protection than fixed-term contracts that allow firms to adjust wages as contracts expire. I use an empirical methodology which captures the direct effects of an immigrant-induced increase in labor supply on the labor market outcomes of natives who have similar skills. I find that the monthly wage of native workers covered by fixed-term contracts decreases in response to immigration, while employment is the margin through which native workers on indefinite-term contracts is affected.
Keywords: F22; J23; J41; 330; Immigration; Wage; Employment; Job contract